Evaluating FEV1 decline in diagnosis and management of pulmonary exacerbations in children with cystic fibrosis. Issue 7 (3rd May 2022) - Bouzek, Drake C.; Ren, Clement L.; Thompson, Misty; Slaven, James E.; Sanders, Don B.
Abstract: Rationale: Forced expiratory volume in 1 s (FEV1) decline (ΔFEV1) is associated with pulmonary exacerbation (PEx) diagnosis in cystic fibrosis (CF). Spirometry may not be available during telehealth visits and could impair clinician ability to diagnose PEx. This study aims to (1) identify the associations between degrees of ΔFEV1 (decrease of <5% predicted vs. 5%−9% predicted vs. ≥10% predicted from baseline), clinical symptoms, and clinician‐diagnosed PEx and (2) evaluate the correlation between respiratory symptoms, ΔFEV1, and antibiotic treatment. Methods: Retrospective, descriptive study of PEx diagnosis and management in 628 outpatient clinical encounters with spirometry in 178 patients with CF ages 6−17 years at Riley Hospital for Children during 2019. Odds ratios (OR) of symptoms associated with clinician‐defined PEx diagnosis and antibiotic management stratified by ΔFEV1 decline were determined. Results: Clinician‐diagnosed PEx occurred at 199 (31.7%) visits; increased cough (77.4%) and sputum/wet cough (57.8%) were the most frequently reported symptoms. Compared to no ΔFEV1, the odds of a clinician‐diagnosed PEx were increased when ΔFEV15%−9% and ΔFEV1≥10% was present with increased cough (OR 1.56, 95% confidence interval [CI] 1.25−1.94 and OR 1.82, 95% CI 1.52−2.19, respectively), increased sputum (OR 1.59, 95% CI 1.20−2.12 and OR 1.78, 95% CI 1.37−2.32, respectively), and increased cough and sputum together (OR 1.51, 95% CI 1.08−2.13 and OR 1.68, 95% CI 1.22−2.31, respectively). Conclusions: ΔFEV1 is associated with increased likelihood that cough and sputum are diagnosed as a PEx. Spirometry is essential for PEx diagnosis and treatment and is a necessary component of all clinical encounters.